2011
DOI: 10.1038/aja.2011.169
|View full text |Cite
|
Sign up to set email alerts
|

Male sex determination: insights into molecular mechanisms

Abstract: Disorders of sex development often arise from anomalies in the molecular or cellular networks that guide the differentiation of the embryonic gonad into either a testis or an ovary, two functionally distinct organs. The activation of the Y-linked gene Sry (sex-determining region Y) and its downstream target Sox9 (Sry box-containing gene 9) triggers testis differentiation by stimulating the differentiation of Sertoli cells, which then direct testis morphogenesis. Once engaged, a genetic pathway promotes the tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 129 publications
0
48
0
3
Order By: Relevance
“…5G). The transcription factor SOX9 is expressed downstream of SRY, the testis determining factor, and defines the Sertoli cell lineage in the testis (81)(82)(83). The expression of SOX9 did not change irrespective of whether the male fertility was moderately or severely affected in Dicer cKO mutant mice (Fig.…”
Section: ) Note That Gfpmentioning
confidence: 99%
“…5G). The transcription factor SOX9 is expressed downstream of SRY, the testis determining factor, and defines the Sertoli cell lineage in the testis (81)(82)(83). The expression of SOX9 did not change irrespective of whether the male fertility was moderately or severely affected in Dicer cKO mutant mice (Fig.…”
Section: ) Note That Gfpmentioning
confidence: 99%
“…7 The integrated intensity of the Trp fluorescence emission spectrum of the WT complex at 15°C was 2-fold less than that of the free domain, providing evidence for the quenching of one or more Trp side chains; such quenching is presumably due to stabilization of the domain on specific DNA binding leading to more complete desolvation of its hydrophobic core. In accordance with this interpretation, the maximum of the native WT spectrum (355 mm) was blue-shifted relative to its max in 8 M guanidine (364 nm, data not shown).…”
Section: -C)mentioning
confidence: 99%
“…Unlike the free domains, however, relative intensities in the variant DNA complexes correlated with side-chain volume (W70A Ͼ W70L). In all cases, 7 The contribution of Trp-107 to the WT fluorescence spectrum was inferred from comparison of the WT domain and a W107D variant (data not shown).…”
Section: -C)mentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, DAZL is involved in rendering the germ cells competent to enter meiosis and could be the intrinsic signal necessary to initiate meiosis (34). In fetal mouse testes, RAmediated initiation of meiosis is prevented by the action of the RA-degrading enzyme CYP26B1 (1, 2) and subsequently by NANOS2 (3), FGF9 (35,36), DMRT1 (4), and NODAL (37,38). In 2011, the model for RA-induced meiosis was challenged by Kumar et al (39), who found Stra8 expression in fetal ovaries from mice lacking RA synthesis (Raldh -/-) in mesonephros and gonads, thereby suggesting that RA is not the only inducer of Stra8 expression and meiosis.…”
Section: Initiation Of Meiosis In Fetal Ovariesmentioning
confidence: 99%